Hydration and Fluid Needs during Physical Activity - Casa, Douglas J.; Kavouras, Stavros (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Hydration during physical activity is a key component of both performance and safety. Several factors impact hydration, including, but not limited to: environmental conditions, such as heat and humidity; clothing and cooling strategies; individual fluid losses measured by sweat rate, sweat composition, dietary composition, and nutrition behaviors; and individual attitudes and perceptions of thirst. This Special Issue, "Hydration and Fluid Needs During Physical Activity", discusses current knowledge and recommendations for assessing, monitoring, and maintaining sufficient hydration during exercise and sport for a diverse range of populations, sports, and conditions. It consists of eleven peer-reviewed papers that cover several aspects relevant to hydration and physical activity.